2018
DOI: 10.5860/rusq.57.3.6606
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Fake News, Librarians, and Undergraduate Research

Abstract: The recent explosion of “fake news” highlights the need for academic libraries to provide access to reliable information resources and for librarians to instruct students in using them effectively. Providing reliable resources with minimal barriers to access involves cooperation among librarians, publishers, and vendors; however, I suggest that there is tension between our mutual desires to satisfy student demands for instant and perfect results and to encourage them to become persistent and critical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
(7 reference statements)
1
15
0
2
Order By: Relevance
“…Information literacy related publications highlighted the need for educating the public on being able to identify fake news, as well as the benefits of having information literacy as a life skill [1,9,17]. It was shown that students are often misinformed about the potential benefits of library services.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Information literacy related publications highlighted the need for educating the public on being able to identify fake news, as well as the benefits of having information literacy as a life skill [1,9,17]. It was shown that students are often misinformed about the potential benefits of library services.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Although there are many studies involving fake news and tools on how to detect it, there is a limited amount of academic work that focuses on the need to encourage information literacy so that people are able to critically access the information they have been presented, in order to make better informed decisions [9].…”
Section: Fake News Todaymentioning
confidence: 99%
See 3 more Smart Citations